Inter-limb gait asymmetry in people with Parkinson's disease - Barbieri, Fabio Augusto [UNESP]; de Campos, Débora da Silva Fragoso; Fukuchi, Claudiane Arakaki [UNESP]; Cupertino, Layla; Pellegrino, Nathalia Mendes; Los Angeles, Emanuele; Coelho, Daniel Boari (Elsevier, 2025)
Gait asymmetry is a hallmark of Parkinson's disease (PD), contributing to instability, increased fall risk, and reduced quality of life. While spatiotemporal asymmetry has been widely studied, limited research has examined joint kinematic asymmetries throughout the gait cycle, particularly in both ON- and OFF-medication states. This study evaluated inter-limb asymmetry in lower limb angular kinematics during walking in individuals with PD compared to neurologically healthy older adults. Twenty-three individuals with PD and 18 healthy older adults participated. PD participants were evaluated in ON- and OFF-medication states. A motion capture system recorded angular kinematics of the hip, knee, ankle, and pelvis during a 10-m walk. Spatiotemporal gait parameters, including step length and stride time, were analyzed alongside joint angular displacement. Statistical Parametric Mapping (SPM) assessed temporal asymmetries between the more and less affected sides. Healthy older adults exhibited no significant asymmetry in joint kinematics. People with PD showed kinematic asymmetries, in both ON and OFF-states, for hip (34 % and 47 % of gait cycle, respectively), knee (30 % and 23 % of gait cycle, respectively), and ankle (29 % of gait cycle - only in OFF-state) movements. Medication had limited effects on reducing kinematic asymmetries. People with PD showed angular asymmetries in the hip, knee, and ankle during different gait cycle phases in ON and OFF states. Detecting significant asymmetry in lower limb angular kinematics suggests that therapeutic approaches should be tailored to address specific inter-limb differences.